Walking it off : a veteran's chronicle of war and wilderness - Peacock, Doug (Eastern Washington University Press, 2005)
"Doug Peacock's tale brings us epic personalities, traumatizing war, grizzly bears, and wildass adventure. A former Green Beret medic in Vietnam, he was mythologized by Edward Abbey as George Washington Hayduke in his environmental classic The Monkey Wrench Gang. Peacock has since become celebrated for his wildlife writing, his book Grizzly Years, and his tireless struggle to help preserve what is wild both in and around us."--BOOK JACKET.